STRATEGI PENGEMBANGAN SDM SYARIAH MENGHADAPI PASAR GLOBAL - Rukiah Lubis (Institut Agama Islam Negeri Padangsidimpuan, 2015)
In the global competitive market, the most perceived challenge is available human resources. in the development of the Islamic economic system is felt there is an imbalance in the provision of human resources. Long run strategic that can do. First, to support the financial educational institution and sharia business. Two, to make more regulation of human development. the third, Islamic economic socialization of the community head. short-run strategy is the first, to integrate the training and education of the Islamic economic system. Both increasing quality of supervision and monitoring systems. Third optimizing BNSP Certification for professional work.